Aplikasi Mobile Pengenalan Huruf Dan Angka Untuk Anak TK Menggunakan Android Studio - Kohirun, Moh.; Arief Yulianto, Muhamad (CV. Shofanah Media Berkah, 2023)
Dewi Sartika Kindergarten is one of the educational places for children in the Kp. Duren Sawit, Ex. Taju, Ciledug district. The learning process of children at an early age in kindergarten needs to be watched out for to avoid boredom in learning, and to be able to facilitate understanding in the learning process. The learning materials provided in the learning process are taken from the child's life processes aimed at facilitating understanding in children's learning. Android is one of the most popular mobile platforms in the world. Learning media applications were developed as a means to facilitate student learning activities. From the problems that occur, a mobile-based letter and number learning application will be built. It is hoped that parents can use cellphones as an attraction for children in learning, especially to recognize letters and numbers. In this application there are image and audio features to make learning the application easier. The results obtained from this research is to create an application that will help teach in teaching about the introduction of letters and numbers they are while carrying a cellphone that has the learning application installed.